Newer disease modifying treatments in pediatric onset multiple sclerosis: Experience from a single center. (July 2022) - Solmaz, Ismail; Acar Ozen, Pınar; Parlak, Safak; Tuncer, Aslı; Anlar, Banu
Abstract: Background: Disease modifying treatments (DMTs) for multiple sclerosis include injectable drugs (iDMTs) like interferons (IFNs) or glatiramer acetate (GA), and newer agents (nDMTs) in oral and intravenous forms. nDMTs are usually applied in escalation and less frequently as initial treatment in pediatric-onset (POMS). Objective: We intended to evaluate the effect of nDMTs in comparison with iDMTs by retrospective examination of our patients with POMS. Method: Clinical records of POMS cases who received nDMTs either as escalation or initial treatment and who had at least 12 months' follow-up in our clinic were examined in two groups: patients who were started on iDMTs and later switched to nDMTs (Group A), and those who received nDMTs from the beginning (Group B). Presenting symptoms, annualized relapsing rate (ARR), recent Expanded Disability Status Scale (EDSS), lesion load and presence of contrast enhancing (CE) lesions on magnetic resonance imaging (MRI) were compared. Results: Total 43 patients were included: 33 in Group A and 10 in Group B. Age at onset, female/male ratio, duration since disease onset and duration under nDMT were similar in both groups. Initial involvement was predominantly brainstem and cerebellar in Group A and sensorial, brainstem/cerebellar, and optic nerve in Group B. The most frequently used nDMT was fingolimod in Group A (n = 17, 51.5%) and teriflunomide (n = 6, 60%) in Group B. Median ARR before any treatment was 2 in Group A and 1.5 in Group B (p > 0.05); it decreased to median 1 under iDMTs in Group A and to 0 under nDMTs. Mean follow-up was 6.7 ± 5 years (1–19, median 6 years) in Group A and 3.9 ± 3.7 years (range 1–12, median 2 years) in Group B. At the latest follow-up median EDSS scores were 1 in Group A and 0 in Group B. ARR had increased and lesion load on MRI went up progressively in both groups during follow-up. However, the rate of patients with CE lesions diminished in Group B. Conclusion: This single-center study of POMS shows the ARR decreases under any treatment, more markedly under nDMTs, and nDMTs reduce the rate of patients with CE lesions on MRI without a clear effect on lesion load. The ARR tends to increase after the first 2 years of both iDMT and nDMT, suggesting a re-evaluation at that time. The ARR decreases shorty after treatment is changed from an iDMT to a nDMT. Highlights: Newer agents reduce relapse rate more effectively in the first years of POMS. Frequent choices were teriflunomide in initial and fingolimod in escalation phases. Critical evaluation of treatment is advisable after 2 years of treatment.